Novel MRI Signs in Atlantodental Space Predict Reduction Degree of Atlantoaxial Dislocation - Xia‐Qing Sheng; Yi‐Fei Deng; Cheng‐Yi Huang; Nan‐Fang Pan; You‐Jin Zhao; Qi‐Yong Gong; Quan Gong; Yue‐Ming Song; Hao Liu; Yang Meng (Orthopaedic Surgery)
ABSTRACT Objective The type of atlantodental space tissue in patients with atlantoaxial dislocation (AAD) can help doctors understand the possibility of reduction before surgery. However, relevant research on this topic is lacking. This study aimed to summarize cases of AAD, classified based on the atlantodental space using magnetic resonance imaging (MRI), and preliminarily explore its impact on the degree of reduction. Methods Preoperative T2‐weighted MRIs and dynamic digital radiographs of patients who underwent posterior reduction and fixation surgery for congenital AAD between September 2012 and February 2023 were collected. The patients were classified into flexible and inflexible tissue sign groups based on T2‐weighted imaging. Patients with an atlantodental interval < 3 mm on extension digital radiography were considered radiographically reducible. Three radiologists read and recorded the MRI results using standard protocols. Kappa and Fleiss kappa values were used to evaluate intra‐ and inter‐observer agreements for MRI signs and dynamic digital radiography findings. Multivariate logistic regression and receiver operating characteristic curves were used to analyze the relationships between imaging parameters and the reduction degree. Results In total, 118 patients with AAD were included in the analysis. Inter‐observer agreement among the three readers was higher for MRI than for dynamic digital radiography (0.816 vs. 0.668). The intra‐observer consistency for MRI signs was also better than that of dynamic digital radiography. Both the flexible tissue sign and radiographically reducible groups showed a higher rate of satisfactory reduction. However, only the flexible tissue sign showed positive results in the multivariate regression. The receiver operating characteristic curve for MRI signs as a predictor of satisfactory reduction yielded an area under the curve of 0.776 (95% confidence interval, 0.667–0.875, p < 0.0001). Conclusions Novel MRI signs of the atlantodental space exhibited high inter‐ and intra‐observer agreement. Patients with flexible tissue signs were more likely to achieve satisfactory reduction after direct posterior surgery.